2012
DOI: 10.1099/vir.0.043364-0
|View full text |Cite
|
Sign up to set email alerts
|

Hantaviruses in rodents and humans, Xi’an, PR China

Abstract: Xi'an, the capital of Shaanxi province, located in north-west China, is one of the major endemic areas for haemorrhagic fever with renal syndrome (HFRS). In this study, the epidemiological data of HFRS in Xi'an from 1959 to 2010, especially in the past ten years (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), were surveyed. The features of hantavirus (HV) host carriers, the molecular characteristics of the HV S gene from hosts and patients, and the genome of the viral isolate were also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 41 publications
3
47
0
Order By: Relevance
“…Serum samples were sent to the Shaanxi Centre for Disease Control and Prevention (CDC) for the detection of hantavirusreactive antibodies. Serological and genetic analyses confirmed that all HFRS cases were caused by HTNV (25,45). In our study, epidemiological data were collected from the Shaanxi Provincial Notifiable Disease Surveillance System.…”
Section: Methodssupporting
confidence: 55%
“…Serum samples were sent to the Shaanxi Centre for Disease Control and Prevention (CDC) for the detection of hantavirusreactive antibodies. Serological and genetic analyses confirmed that all HFRS cases were caused by HTNV (25,45). In our study, epidemiological data were collected from the Shaanxi Provincial Notifiable Disease Surveillance System.…”
Section: Methodssupporting
confidence: 55%
“…Hantaan virus (HTNV), the prototype of the Hantavirus genus, is a rodent-borne pathogen which could cause severe hemorrhagic fever with renal syndrome (HFRS) in human with a mortality rate up to 10% mainly in Asia [1, 2]. Plasma leakage is a hallmark of the syndrome, which is characterized by acute thrombocytopenia, the loss of vascular integrity, and enhanced vascular permeability, leading to hemorrhage in patient days to weeks after infection [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed procedures can be found in published articles. 20 Data on reported HFRS cases in the study area from 2007 to 2010 were obtained from the Hunan Notifiable Disease Surveillance System (HNDSS). All of the cases were initially diagnosed based on clinical symptoms according to diagnostic criteria from the Ministry of Health of the People's Republic of China.…”
Section: Methodsmentioning
confidence: 99%